THE ROLE OF MODERN TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES (International journal of artificial intelligence, 2025)
As we all know, one of the goals and objectives of the educational reform being carried out in our country is to train specialists who can master foreign languages fluently and freely communicate with the younger generation, to introduce them to the culture of the peoples of the world through the study of foreign languages.